A scoping review protocol for exploration of stroke risk factors among women in Africa - Sakina Sule Ali; Sham’unu Isah Abdu; Umar Muhammad Bello; Isa Usman Lawal (Discover Public Health)
Abstract Background Stroke is a leading cause of mortality and disability globally, with an increasing burden in low- and middle-income countries, including those in Africa. While stroke affects both men and women, emerging evidence suggests that women may face unique risk factors and challenges that contribute to their susceptibility to stroke. However, there is a lack of comprehensive understanding regarding the specific risk factors for stroke among women in Africa. Purpose This scoping review protocol aims to systematically explore and map the existing literature on stroke risk factors among women in Africa. Method The review will follow the methodological framework outlined by Arksey and O'Malley, enhanced by the Joanna Briggs Institute guidelines for scoping reviews. A systematic search will be conducted across multiple electronic databases, including Cochrane Library, Web of Science, EBSCO, Medline and Google Scholar, using a predefined search strategy. The search strategy will include a combination of keywords and Medical Subject Headings (MeSH) terms related to stroke, risk factors, women, and Africa. Result Data extraction will involve the systematic recording of relevant information from included studies, including study characteristics, participant demographics, stroke risk factors examined, and key findings. Thematic analysis will be conducted to identify common themes and patterns across the literature, with a particular focus on risk factors specific to women in Africa. Conclusion This scoping review will provide a comprehensive overview of the current state of knowledge regarding stroke risk factors among women in Africa. Findings from this review will inform future research directions, clinical practice, and public health interventions aimed at reducing the burden of stroke among women in the African context.